Pengaruh Model Pembelajaran Problem Based Learning Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas IX SMP N 1 Salak Kabupaten Pakpak Bharat Tahun Ajaran 2023/2024 - Juliana Padang; Oktober Tua Aritonang; Pestaria Naibaho (Publisher STPKat, 2023)
The aim of this research is to determine the positive and significant influence of the Problem Based Learning Model on the Learning Motivation of Christian Religious Education in Class IX Students of SMP N 1 Salak, Pakpak Bharat Regency, Academic Year 2023-2024. The research method used is a quantitative research method and a pre-experimental design research type in the form of